GAMBARAN PERILAKU SELF- INJURY PADA SISWA SEKOLAH RAKYAT MENENGAH PERTAMA 24 GOWA - Nirwana Sabrina; Nur Fadhilah Umar; Aswar; Nurfaidah Ardis (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study is motivated by the increasing prevalence of self-injury behavior among adolescents and the limited research within alternative educational settings such as Sekolah Rakyat. The aim of this study is to describe self-injury behavior among students at Sekolah Rakyat Menengah Pertama (SRMP) 24 Gowa. A descriptive quantitative approach was employed using total sampling involving 105 seventh-grade students. Data were collected through a self-injury scale that has been tested for validity and reliability, which revealed that almost half of adolescents (46.5%) had committed self-injury in the past year, with 28% of them categorized as moderate to severe. and supported by interviews. Data analysis was conducted using descriptive statistics. The results indicate that the level of self-injury is in the high category, with a mean score of 3.41. The most common behaviors were minor self-injury, such as hitting oneself and picking at wounds, while a small proportion engaged in major self-injury, such as cutting. Contributing factors include emotional instability, maladaptive beliefs, peer influence, and family background. These findings highlight that self-injury serves as a maladaptive coping mechanism. Therefore, preventive interventions through counseling services focusing on emotional regulation and cognitive restructuring are essential.